Mercy Creek - Browning, M. E. (Browning, M. E. Jo Wyatt mystery, 2021)
"The late summer heat in Echo Valley, Colorado turns lush greenery into a tinder dry landscape. When a young girl mysteriously disappears, long buried grudges rekindle. Of the two Flores girls, Marisa was the one people pegged for trouble. Her younger sister, Lena, was the quiet daughter, dutiful and diligent--right until the moment she vanished. Detective Jo Wyatt is convinced the eleven-year-old girl didn't run away and that a more sinister reason lurks behind her disappearance. For Jo, the case is personal, reaching far back into her past. But as she mines Lena's fractured family life, she unearths a cache of secrets and half-lies that paints a darker picture. As the evidence mounts, so do the suspects, and when a witness steps forward with a shocking new revelation, Jo is forced to confront her doubts, and her worst fears. Now, it's just a matter of time before the truth is revealed--or the killer makes another deadly move."--Provided by publisher.